Untangling the Mechanisms of Lattice Distortions in Biogenic Crystals across Scales - Schoeppler, Vanessa (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH.